Pengaruh Belanja Modal Terhadap Pertumbuhan Ekonomi di Indonesia - Puput Waryanto (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2017)
The purpose of the study was to investigate the influence of capital expenditure on economic growth in Indonesia. The reasons of the study were the inconsistency of previous research results in many countries, the difficulty of achieving national economic growth target, and the low ratio of capital expenditure to Gross Domestic Product (GDP). By using time series data from 1990 to 2015 in Indonesia, this research has proved that the capital expenditure has a significant positive effect on economic growth. On the other hand, the operational expenditure, which consisted of personnel expense, goods and services expenses, interest, subsidies, grants and social assistance, had not a significant effect on economic growth. This study has considered inflation as a control variable. Consequently, the central government should be able to pay attention on capital expenditure, both on its quantity and quality. Abstrak Penelitian ini bertujuan untuk melihat seberapa besar pengaruh belanja modal terhadap pertumbuhan ekonomi di Indonesia. Beberapa hal yang melatarbelakangi penelitian ini adalah masih adanya ketidakkonsistenan hasil penelitian di berbagai negara, masih sulitnya pencapaian target pertumbuhan ekonomi nasional, masih rendahnya rasio belanja modal terhadap PDB. Dengan menggunakan data time series selama 26 tahun mulai 1990 s.d. 2015 di Indonesia, penelitian ini telah membuktikan bahwa belanja modal berpengaruh positif signifikan terhadap pertumbuhan ekonomi, tetapi belanja operasi yang terdiri dari belanja pegawai, belanja barang, bunga, subsidi, hibah, dan bantuan sosial, tidak berpengaruh signifikan terhadap pertumbuhan ekonomi. Penelitian ini telah mempertimbangkan variabel kontrol berupa inflasi. Berkaitan dengan hasil penelitian, pemerintah pusat hendaknya terus memperhatikan belanja modal, baik dari segi kuantitas maupun kualitas belanja modal.